KONTRIBUSI UMKM TERHADAP PENYERAPAN TENAGA KERJA DAN STABILITAS EKONOMI INDONESIA - Dzikri Darmawan (CURVE: Journal of Economic, Business and Accounting, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy as the backbone supporting the sustainability of the national economy. This study aims to identify the quantitative and qualitative contributions of MSMEs to the labor market, analyze their status as pillars of the national economy, and formulate strategies to strengthen their strengths, thereby supporting overall economic stability. The research method used in this study is a qualitative descriptive method with a literature analysis approach (library research). The results indicate that Micro, Small, and Medium Enterprises (MSMEs) make a significant contribution to the national economy, both in employment absorption and in maintaining Indonesia's economic stability. Based on data analysis, the MSME sector is capable of absorbing approximately 97 percent of the total national workforce, or more than 119 million people by 2025.